THE INFLUENCE OF WORK ABILITY AND WORK STRESS ON EMPLOYEE PERFORMANCE AT DR.GL.TOBING GENERAL HOSPITAL TANJUNG MORAWA - Sri Damayanti; Nur Aisyah; Sjahril Effendy (RADJA PUBLIKA, 2023)
This research aims to determine the influence of Work Ability and Job Stress on Employee Performance in. The population of this study was 106 samples. This research was taken using total sampling technique, where the entire population was a sample of 106 people. This research uses quantitative methods. The measuring instruments used are the Work Ability scale, Work Stress scale and Employee Performance scale. Data analysis used multiple linear regression tests. The results of this study indicate that (1) there is an effect of work ability and work stress on employee performance, where a significance value of 0.000 is 0.05, the hypothesis is rejected. This means that the Work Ability variable and the Work Stress variable have a significant influence on employee performance. Many employees' performance currently has problems in carrying out services or at work, so there is an influence on work ability on employee performance. From the results of the statistical analysis, it was found that the t coefficient was 2,750 with p < 0.05 and the correlation coefficient rx1y was 0.713 with p < 0.05, this means that the level of employee ability will be able to influence the level of performance that can be displayed. There is an influence of work stress on employee performance. From the results of statistical analysis it was found that the t coefficient was 1.994 with p < 0.05, and the rx2y correlation coefficient was 0.531 with p < 0.05, thus it can be concluded that the level of work stress experienced by employees will be able to increase or decrease employee performance. There is an influence of work ability and work stress on employee performance. From the results of statistical analysis it was found that the coefficient F reg = 57.727 with p < 0.05, and the correlation coefficient R = 0.727 with p < 0.05 and R2 = 0.529. Thus it can be concluded that work ability and work stress jointly affect employee performance, the contribution of both in improving performance is 52.9%. There are 47.1% other factors or variables that can influence employee performance. the contribution of both in improving performance was 52.9%. There are 47.1% other factors or variables that can affect employee performance. the contribution of both in improving performance was 52.9%. There are 47.1% other factors or variables that can influence employee performance.